Tuberculous Meningitis: Pathogenesis, Clinical Features, Diagnosis, and Treatment (Multidisciplinary Journal of Science and Technology, 2025)
The review of the literature based on modern domestic and foreign literature data presents information on pneumonia in newborn children. Controversial issues of classification and diagnostic criteria of the disease are discussed. Current information on the characteristics, epidemiology of neonatal pneumonia, etiology and specific risk factors of congenital pneumonia, pneumonia with early and late onset, including nosocomial and ventilator-associated pneumonia, community-acquired pneumonia in newborn children is summarized. Data on the frequency of respiratory and general clinical symptoms, results of image diagnostics and laboratory diagnostics of the disease are provided.